Cadmium, zinc and lead in soils in the zone of influence of the industrial enterprises - Golovatyi, Sergey E.; Savchenko, Svetlana V.; Samusik, Elena A. (Journal of the Belarusian State University. Ecology, 2018)
Assessment of the total and mobile forms of cadmium, lead and zinc in a soil cover in the territory of the industrial enterprises has shown pollution of soils these elements. The highest level pollution of soils zinc is noted in a zone of influence of the enterprise of a machine-building com-plex where average concentration of metal has exceeded the standard for the total contents by 7,5 times, for mobile forms – by 1,6 times. The increased contents in soils of the total cadmium is not-ed at industrial sites in a zone of influence of the enterprises for production of cement and ma-chinebuilding production. Pollution of soils mobile lead is characteristic of the enterprises specializing in foundry and cement production where the average content of an element is higher than admissible level in 4,1 and 1,7 times respectively.
Keywords: total and mobile forms of heavy metals; pollution of soils; elements pollutants; industrial enter-prise; threshold limit value